2000
DOI: 10.1152/jappl.2000.88.2.774
|View full text |Cite
|
Sign up to set email alerts
|

Waging war on modern chronic diseases: primary prevention through exercise biology

Abstract: In this review, we develop a blueprint for exercise biology research in the new millennium. The first part of our plan provides statistics to support the contention that there has been an epidemic emergence of modern chronic diseases in the latter part of the 20th century. The health care costs of these conditions were almost two-thirds of a trillion dollars and affected 90 million Americans in 1990. We estimate that these costs are now approaching $1 trillion and stand to further dramatically increase as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
170
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 562 publications
(178 citation statements)
references
References 50 publications
0
170
0
8
Order By: Relevance
“…From these ideas we wrote in 2000 (Booth et al 2000), "…we present the concept that the human genome evolved within an environment of high physical activity. Accordingly, we propose that exercise biologists do not study 'the eVect of physical activity' but in reality study the eVect of reintroducing exercise into an unhealthy sedentary population that is genetically programmed to expect physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…From these ideas we wrote in 2000 (Booth et al 2000), "…we present the concept that the human genome evolved within an environment of high physical activity. Accordingly, we propose that exercise biologists do not study 'the eVect of physical activity' but in reality study the eVect of reintroducing exercise into an unhealthy sedentary population that is genetically programmed to expect physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, approximately 250,000 persons per year in the United States are premature deaths due to physical inactivity (Booth et al 2000). In fact, epidemiological data showed that physical inactivity increased the incidence of at least 17 unhealthy conditions, almost all of which are chronic diseases or considered risk factors for chronic diseases (HoVman et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…B. die Wahrscheinlichkeit von koronarer Herzkrankheit, Apoplex, Hypertonie, Diabetes mellitus Typ 2, einigen Krebsarten, Osteoporose und Arthrose [8,10]. Insgesamt sind bis zu 14% aller vorzeitigen Todesfälle auf Krankheiten durch Bewegungsmangel zurückzuführen.Nach einer Analyse der Verteilung der Gesundheitskosten an 1,2 Mio.…”
Section: Folgen Von Bewegungsmangelunclassified